Advancements in research on psychological and emotional aspects of student-athletes - Mao, Zhoujie (Frontiers in Psychology, 2025)
PurposeThis systematic review synthesizes evidence on the psychological and emotional experiences of collegiate student-athletes, identifying key stressors, coping strategies, and intervention effectiveness.MethodsLiterature was searched in PubMed, PsycINFO, Scopus, and Web of Science for studies published between 2010 and 2024. A total of 41 empirical studies met inclusion criteria (27 cross-sectional, 7 longitudinal/observational, 4 quasi-experimental/experimental, and 3 mixed-methods). The studies were conducted primarily in the USA (n = 19), Europe (n = 11), and East Asia (n = 8), with sample sizes ranging from 30 to >1,000 participants.ResultsAcross studies, the most frequently reported stressors were training load (68% of studies), academic pressure (61%), and coach-athlete or team dynamics (42%). Emotional outcomes included anxiety (reported in 70% of studies), depression (52%), and burnout/fatigue (39%). Quantitative data indicated that depressive symptoms affected up to 35% of female student-athletes and COVID-related disruptions increased distress levels in over 40% of participants. Coping strategies with strongest empirical support included Psychological Skills Training (PST) (9 studies), Cognitive-Behavioral Therapy (CBT) (3 studies), and self-care practices such as sleep hygiene and mindfulness (11 studies).ConclusionStudent-athletes’ well-being is shaped by the dual demands of sport and academics, moderated by gender and cultural context. Evidence supports PST and CBT as effective interventions, complemented by self-care practices. To translate these findings into practice, universities and sports organizations should integrate structured mental skills programs into athletic training, provide flexible academic support during peak competition periods, and invest in accessible counseling services. Policy efforts should focus on reducing stigma, training coaches and staff to recognize early signs of distress, and expanding digital or mobile-based mental health solutions to increase accessibility.